THE ANALYSIS OF SCAFFOLDING UTILIZATION RISK LEVEL ON CONSTRUCTION COMPANY OF MULTISTORIED BUILDING - SANAN NIM: 25314702, JEFRIANUS
The high number of work accidents in the construction sector requires construction companies to establish regulations in suppressing the number of work accidents. However, the number of work accidents in the construction sector, such as the danger of falling from a height, is still relatively high. Scaffolding is a temporary construction that built up as an access to work at certain altitude of more than 2 meters. This research was conducted at PT.X on the construction project of 4-floored Student Activity Center Building located in Bandung. The purposes of this study are to determine the type of work with the highest risk value using scaffolding and to determine the risk value of it. The methods used in this research were the Semi-Quantitative method and Failure Mode Effect Analysis (FMEA). The primary data were obtained by interview, observation, questionnaires and documentation. This research required some secondary data like work accident data and work procedures from K3 project experts related to scaffolding installation, ACP structure, electrical-mechanical, architecture, installation of roster and finishing work data. The results of risk analysis show that the highest risk value are on the electrical mechanical work group with the risk value of 540 (very high category) and the highest RPN value is on the architecture work unit of 336 (Priority 1 category). Based on the analysis, risk control needs to be carried out systematically improvement of the K3 implementation, starting from the management, K3 supervisors and workers.